Optimalisasi Pemanfaatan Lahan Pekarangan Untuk Mendukung Ketahanan Pangan Rumahtangga Petani Lahan Kering Di Desa Kayangan Lombok Utara - Jayaputra Jayaputra; Nurrachman Nurrachman; Bambang Budi Santoso; I Komang Damar Jaya (Fakultas Pertanian Universitas Mataram, 2020)
Agricultural land in Kayangan Village is mostly dry land with relatively low productivity and diversification of food production, which affects the income and supply of food that is not diverse and nutritious that affects the nutritional status of all family members and threatens household food security. However, the average household has a fairly large yard, which if properly designed and managed, will be able to meet the family's own food and nutrition needs, also has the opportunity to increase household income. The potential of the plots in the village of Heaven has not been managed properly, due to the low awareness of the importance of their plots, lack of knowledge and skills regarding proper yard management techniques to meet food and nutrition needs and family income. To overcome these problems, innovation technology transfer has been carried out through the development of environmentally friendly horticultural crops in optimizing the use of the yard to meet the nutritional needs and family income. Counseling and training / demonstration plots have been carried out during June-December 2019. Community service activities are considered quite successful in terms of the enthusiasm and perseverance of the participants in participating in this mentoring activity. The results of the demonstration plot showed a significant increase both in crop productivity and plant diversity that can be cultivated on the plots. Ongoing assistance from all parties, especially the local government, is expected to sustainably develop yard use to increase food availability and fulfill family nutrition, increase income and household food security of dry land farmers.